The Utility of Zebrafish as a Model for Screening Developmental Neurotoxicity - d’Amora, Marta; Giordani, Silvia (Frontiers in Neuroscience, 2018)
The developing central nervous system and the blood brain barrier are especially vulnerable and sensitive to different chemicals, including environmental contaminants and drugs. Developmental exposure to these compounds has been involved in several neurological disorders, such as autism spectrum disorders as well as Alzheimer’s and Parkinson’s diseases. Zebrafish (Danio Rerio) have emerged as powerful toxicological model systems that can speed up chemical hazard assessment and can be used to extrapolate neurotoxic effects that chemicals have on humans. Zebrafish embryos and larvae are convenient for high-throughput screening of chemicals, due to their small size, low-cost, easy husbandry, and transparency. Additionally, zebrafish are homologous to other higher order vertebrates in terms of molecular signaling processes, genetic compositions, and tissue/organ structures as well as neurodevelopment. This mini review underlines the potential of the zebrafish as a complementary model for developmental neurotoxicity screening of chemicals and describes the different endpoints utilized for such screening with some studies illustrating their use.